2013
DOI: 10.1002/cphc.201300686
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for the Extraction of Metals from Water to Ionic Liquids

Abstract: We present a novel mechanism for the extraction of metals from aqueous phases to room-temperature ionic liquids (ILs) by use of a high-temperature salt as an extraction agent. The mechanism capitalizes on the fact that charged metal complexes are soluble in ILs; this allows for extraction of charged complexes rather than the neutral species, which are formed by conventional approaches. The use of a well-chosen extraction agent also suppresses the competing ion-exchange mechanism, thus preventing degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
(39 reference statements)
4
26
0
Order By: Relevance
“…The observed anion:copper ratios do not necessarily indicate that the anions are coordinated with the copper, as previous work indicates that charged metal complexes are soluble in ILs [14,15] and uncoordinated ions can move into the IL phase in tandem with a charged metal complex to maintain electroneutrality [59,60]. As indicated in Table 3, all three mineral anions used in the present study coordinate relatively weakly with copper(II).…”
Section: Extractions Involving a Single Copper Saltmentioning
confidence: 52%
See 1 more Smart Citation
“…The observed anion:copper ratios do not necessarily indicate that the anions are coordinated with the copper, as previous work indicates that charged metal complexes are soluble in ILs [14,15] and uncoordinated ions can move into the IL phase in tandem with a charged metal complex to maintain electroneutrality [59,60]. As indicated in Table 3, all three mineral anions used in the present study coordinate relatively weakly with copper(II).…”
Section: Extractions Involving a Single Copper Saltmentioning
confidence: 52%
“…Ion exchange mechanisms involving metals and IL cations have been studied extensively [55][56][57][58][59][60], and it is observed that strongly hydrophobic cations such as 1-decyl-3-methylimidazolium generally do not undergo extensive ion exchange [61]. The trialkylammonium species in the ILs used in the current study are sufficiently hydrophobic that it would be quite surprising if they engaged in ion exchange to a significant degree.…”
Section: Mechanism Of Extractionmentioning
confidence: 93%
“…Both the cation and anion, however, must be extracted to maintain electroneutrality. We have demonstrated17 that the method not only provides high yields in extracted ions, it also suppresses the ion exchange mechanism noted in the Introduction, preserving the integrity of the IL. Note that this is distinct from conventional salting out approaches used to precipitate biomolecules.…”
Section: Theorymentioning
confidence: 88%
“…We have shown previously17 that the extraction of ions from aqueous to IL phase can be promoted by using a salt as a co‐extractant. The process is shown schematically in Figure 2.…”
Section: Theorymentioning
confidence: 99%
“…Nevertheless, extraction studies in ILs are often conducted with the goal of promoting a neutral extraction mechanism over ion exchange. This is achieved by controlling the components of the IL, the extractant, and the aqueous phase (often empirically) so that the extracted metal species is neutral [51,52].…”
Section: Inner-sphere Interactions Between Metal Ionsmentioning
confidence: 99%